Pengaruh Tambahan Penghasilan Pegawai terhadap Kinerja Pegawai Negeri Sipil di Kantor Kecamatan Kesugihan - Suranto Suranto; Tofan Tri Nugroho (Syntax Corporation Indonesia, 2024)
Cilacap Regent Regulation No. 03 of 2024, which addresses the Provision of Additional revenue to State Civil Apparatus Employees in the Regional Government, provides civil servants in the Kesugihan Subdistrict Office, Cilacap Regency with sources of revenue beyond their salary and allowances. One way to show gratitude for the work that state civil apparatus employees do is to give them a raise. This will have a positive impact on their morale, productivity, and overall well-being. This prompted the author to investigate whether or not the Cilacap Regency Government's civil officials, and those working in the Kesugihan District Office in particular, would be more productive after receiving a salary increase. The author's research shows that in the Kesugihan District office setting, additional employee income does have an effect on civil servants' performance, but that this effect is not yet optimal and requires additional attention from leadership to achieve maximum results. The Kesugihan District Office's civil servants could benefit from additional employee income (TPP) in the form of higher wages and better working conditions, as well as more discipline, which should lead to better service delivery.